2014
DOI: 10.1136/bjophthalmol-2013-304477
|View full text |Cite|
|
Sign up to set email alerts
|

Photobiomodulation in the treatment of patients with non-center-involving diabetic macular oedema

Abstract: Purpose Far-red/near-infrared phototherapy or photobiomodulation (PBM) has recently been reported to be an effective and non-invasive treatment method to inhibit lesions of diabetic retinopathy (DR) in animals. This study investigated the safety and efficacy of PBM in diabetic patients to treat non-center-involving diabetic macular oedema (NCDME). Methods This was a non-randomised, consecutive, case series, where 4 patients with type 2 diabetes with NCDME were treated for 160 s per day with PBM for 2–9 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 5 publications
(4 reference statements)
1
56
0
Order By: Relevance
“…89e92 Studies related to the retina likewise have demonstrated that the low-intensity far-red (670 nm) light treatment mitigates pathology in retinal degeneration models 93,94 and, recently, also in DR. 95,96 In both diabetic albino rats 96 and pigmented mice, 97 whole-body exposure to far-red light (670 nm) for only 4 minutes per day from the onset of diabetes or as an intervention mitigated abnormalities that are believed to contribute to DR, including increased generation of superoxide, induction of a local proinflammatory environment, and dysfunction or degeneration of retinal neurons. Consistent with this, daily photobiomodulation administered to a small series of diabetic patients having nonecenterinvolved macular edema was associated with the gradual reduction in retinal thickness.…”
Section: Photobiomodulationmentioning
confidence: 99%
See 1 more Smart Citation
“…89e92 Studies related to the retina likewise have demonstrated that the low-intensity far-red (670 nm) light treatment mitigates pathology in retinal degeneration models 93,94 and, recently, also in DR. 95,96 In both diabetic albino rats 96 and pigmented mice, 97 whole-body exposure to far-red light (670 nm) for only 4 minutes per day from the onset of diabetes or as an intervention mitigated abnormalities that are believed to contribute to DR, including increased generation of superoxide, induction of a local proinflammatory environment, and dysfunction or degeneration of retinal neurons. Consistent with this, daily photobiomodulation administered to a small series of diabetic patients having nonecenterinvolved macular edema was associated with the gradual reduction in retinal thickness.…”
Section: Photobiomodulationmentioning
confidence: 99%
“…Consistent with this, daily photobiomodulation administered to a small series of diabetic patients having nonecenterinvolved macular edema was associated with the gradual reduction in retinal thickness. 95 Arden et al 98 likewise used light to exert a beneficial effect on DME. In one study, they used trans-eyelid retinal illumination of one eye in patients with DR during sleep throughout a 3-month period, and found a reduction in the number of hemorrhages and microaneurysms compared to the contralateral eyes.…”
Section: Photobiomodulationmentioning
confidence: 99%
“…Animal studies using albino rats and pigmented mice showed that whole-body photobiomodulation inhibited diabetes-induced abnormalities in retinal oxidative stress, inflammation, and electroretinogram [31,38], and very effectively inhibited diabetes-induced increases in capillary degeneration and accumulation of albumin in neural retina (unpublished). In a case report series of diabetic patients having non-center involved retinal edema, application of the same wavelength of light for an equally short interval daily showed beneficial effects to reverse the edema in the treated eye [39]. …”
Section: Do Retinal Photoreceptors Contribute To Vascular Lesions Of Dr?mentioning
confidence: 99%
“…Further, PBM has recently been shown to reduce non‐central diabetic macular oedema in a case series (Tang et al. 2014). …”
Section: Introductionmentioning
confidence: 99%